1927
DOI: 10.1152/ajplegacy.1927.79.2.305
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Vitamins B and E to Fertility in the Male Rat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1929
1929
1983
1983

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the introduction to this paper, attention was drawn to the circumstantial and indirect nature of much of the evidence apparently showing that the effect of unsaturated fat stress was on the metabolism of tocopherol itself. We have examined the literature on the subject from the original observation of Mattill (1927) to the present, in an attempt to ascertain whether the results of our experiments are contradicted by others. It is perhaps not surprising that there have been few quantitative studies on the effect of fat on tocopherol metabolism in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the introduction to this paper, attention was drawn to the circumstantial and indirect nature of much of the evidence apparently showing that the effect of unsaturated fat stress was on the metabolism of tocopherol itself. We have examined the literature on the subject from the original observation of Mattill (1927) to the present, in an attempt to ascertain whether the results of our experiments are contradicted by others. It is perhaps not surprising that there have been few quantitative studies on the effect of fat on tocopherol metabolism in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…The theory that vitamin E functions solely as a biological antioxidant rests on two main pillars of experimental work, the first being the effect of fat in vitamin E deficiency disease, the second the simulation (generally only partial) of vitamin E activity by some synthetic dyes and antioxidants. The role of fat in vitamin E deficiency was known to early workers in the field, Mattill (1927) first showing that vitamin E deficiency in the rat could be accelerated by rancidity of the dietary fat. Pappenheimer & Goettsch (1931) first showed that a high-fat diet was necessary to produce encephalomalacia in chickens, and Madsen, McCay & Maynard (1935) noted that the addition of cod-liver oil to diets deficient in vitamin E accelerated the onset of muscular dystrophy in rabbits and guinea-pigs.…”
mentioning
confidence: 99%